2006
DOI: 10.1104/pp.106.089615
|View full text |Cite
|
Sign up to set email alerts
|

TheMi-9Gene fromSolanum arcanumConferring Heat-Stable Resistance to Root-Knot Nematodes Is a Homolog ofMi-1 

Abstract: Resistance conferred by the Mi-1 gene from Solanum peruvianum is effective and widely used for limiting root-knot nematode (Meloidogyne spp.) yield loss in tomato (Solanum lycopersicum), but the resistance is ineffective at soil temperatures above 28°C. Previously, we mapped the heat-stable resistance gene Mi-9 in Solanum arcanum accession LA2157 to the short arm of chromosome 6, in a genetic interval as Mi-1 and the Cladosporium fulvum resistance gene Cf2. We developed a fine map of the Mi-9 region by resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 48 publications
1
66
0
3
Order By: Relevance
“…Some genes have been found to have important roles in resistance against nematodes and aphids, such as SlWRKY72a, HSP90, LeMPK2, LeMPK1, LeMPK3, SlSERK1, and SGT1 [116][117][118][119][120]. Suppressing threonine deaminase (TD) and germin-like, jasmonateresistant4 (JAR4) by VIGS confirmed that these genes have important roles in activating plant defenses to M. sexta [121,122].…”
Section: Genes Involved In the Defense Response To Pathogens Insectsmentioning
confidence: 83%
“…Some genes have been found to have important roles in resistance against nematodes and aphids, such as SlWRKY72a, HSP90, LeMPK2, LeMPK1, LeMPK3, SlSERK1, and SGT1 [116][117][118][119][120]. Suppressing threonine deaminase (TD) and germin-like, jasmonateresistant4 (JAR4) by VIGS confirmed that these genes have important roles in activating plant defenses to M. sexta [121,122].…”
Section: Genes Involved In the Defense Response To Pathogens Insectsmentioning
confidence: 83%
“…A moderate increase in temperature inhibits defense responses mediated by a number of R genes, including N, Mi, RPS4, and SNC1 (Dropkin, 1969;Malamy et al, 1992;Jablonska et al, 2007;, whereas a chilling temperature is required for some gain-offunction mutants in R or R-related genes to induce defense responses (Huang et al, 2010;Yang et al, 2010). Recently, it has been shown that R genes could be the temperature-sensitive component in defense responses, and alteration of R protein activity can change temperature sensitivity of the defense responses (Zhu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It could be expected that certain philogenetic relationships may change as more taxons are further added in future studies using this method. Finally, it is interesting to observe that S. peruvianum TS-403 lies within the Eriopersicon informal group, whilst S. peruvianum TS-402 lies within the Arcanum informal group, which can be readily accounted for when considering that the first corresponds to S. peruvianum (north) variety whilst the second corresponds to S. peruvianum (south) variety 26 .…”
Section: Discussionmentioning
confidence: 97%
“…Peralta and Spooner 8 included S. peruvianum North within Arcanum group and S. peruvianum South within the Eriopersicon group. This comes as no surprise given the fact that that TS-404 and TS-403 correspond to the S. peruvianum South variety, whilst TS-402 corresponds to the S. peruvianum North variety 26 . In the filtered supernetwork, the three principal Lycopersicon subgroups are clearly separated, with the S. pimpinellifolium distributed among the three, and all four of them closely connected to the nodes separating these three subgroups, which consequently indicates a close relationship between them.…”
Section: /13mentioning
confidence: 94%